The Importance of Advices and Teachings In The Book "Ta’lim Al-Muta’allim" - Reimberganovich, Turayev Davronbek (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article talks about "Ta’lim al-mutaallim", the book by the scientist Burkhaniddin al-Zarnuji, an islamic scholar who lived in the 12th-13th centuries AD, and the necessary manners, advices and instructions for acquiring knowledge covered in this book. Also provides such information are shown to be substantiated with the help of reliable sources. This work of the scholar, as a key book on the path to gain knowledge, has been in the hands of students for centuries.